2019
DOI: 10.1161/circinterventions.118.007281
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Trimethylamine N-Oxide as a Novel Biomarker for Plaque Rupture in Patients With ST-Segment–Elevation Myocardial Infarction

Abstract: Background: Trimethylamine N-oxide (TMAO) is reported to promote the pathogenesis of atherosclerosis and be associated with cardiovascular events risk. It is unknown whether plasma TMAO is associated with plaque morphology in patients with acute myocardial infarction. We investigated the relationship between the culprit plaque morphology and plasma TMAO concentration in patients with ST-segment–elevation myocardial infarction. Methods and Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 32 publications
4
59
0
1
Order By: Relevance
“…[ 15 ] Another prospective series of 211 patients with STEMI demonstrated higher TMAO levels association with plaque rupture assessed by optical coherence tomography examination and these findings have significant adverse risks in CVD patients. [ 22 ] The association of TMAO with atherosclerosis burden in stable coronary artery disease has also been reported previously. [ 21 ] In light of these promising findings, the evaluation TMAO and TML are warranted in NSTEMI patients as represent the most frequent group of CVD patients undergoing pPCI, which may serve as a potential target for atherosclerosis prevention and treatment as compared with present traditional treatments.…”
Section: Discussionsupporting
confidence: 57%
“…[ 15 ] Another prospective series of 211 patients with STEMI demonstrated higher TMAO levels association with plaque rupture assessed by optical coherence tomography examination and these findings have significant adverse risks in CVD patients. [ 22 ] The association of TMAO with atherosclerosis burden in stable coronary artery disease has also been reported previously. [ 21 ] In light of these promising findings, the evaluation TMAO and TML are warranted in NSTEMI patients as represent the most frequent group of CVD patients undergoing pPCI, which may serve as a potential target for atherosclerosis prevention and treatment as compared with present traditional treatments.…”
Section: Discussionsupporting
confidence: 57%
“…Plasma TMAO concentrations were significantly higher in patients with ST-segment elevation myocardial infarction with plaque rupture than in patients exhibiting plaque erosion. The authors suggested that TMAO could be a useful biomarker for predicting plaque rupture in patients with a history of acute myocardial infarction [26].…”
Section: Tmao and Cvdmentioning
confidence: 99%
“…10 Recently, TMAO has emerged as a significant mediator, demonstrating a close relationship between gut microbiota and multiple CVDs such as atherosclerosis, hypertension, diabetes, and myocardial infarction. [11][12][13][14][15] Remarkably, TMAO is also a powerful prognostic marker, participating in the progression of HF. 16 Subsequent preclinical experiments show that TMAO may directly affect the heart by inducing myocardial hypertrophy and fibrosis, endothelial cell and vascular inflammation, as well as cardiac mitochondrial dysfunction, thereby aggravating the progress of HF.…”
Section: Introductionmentioning
confidence: 99%